SURVEYS OF SIAMESE CROCODILE (Crocodylus siamensis) HABITAT IN THE MAHAKAM RIVER, EAST KALIMANTAN - Hellen - Kurniati (ZOO INDONESIA, 2007)
Kurniati, H. 2007. Survey of Siamese crocodile (Crocodylus siamensis) habitat inthe Mahakam River, East Kalimantan. Zoo Indonesia 16 (2): 51-62. A survey wasundertaken to collect information on C. siamensis habitats and possible locationswhere C. siamensis occur in the lower Makaham River, East Kalimantan. Interviewswith local villagers confirmed that C. siamensis were still encountered, and thatbreeding still occurs. Specific wild habitats visited (Tanah Liat, Paya, Belibis, Amir &Mesangat Lakes) had changed greatly since 1995-1996, but weeds and sedimentationwere identified as impacting negatively on the habitats. Fishing pressure hadincreased in recent years, and young crocodiles were being caught during fishingactivities. Around 360 C. siamensis were currently in captivity at two crocodile farmsand in villages in the Mahakam River area. Hybridization with C. porosus had occurredon one of the farms.